2019
DOI: 10.1371/journal.pone.0219849
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the stage of osteoarthritis before and six months after tibial tuberosity advancement procedure in dogs

Abstract: The present retrospective study evaluated the progression of osteoarthritis in stifle joints based on the radiographic grade of osteoarthritis (OA) scored in dogs with cranial cruciate ligament rupture. The aim of the study was to search for a correlation between the stage of radiographic osteoarthritis prior to surgery and the osteoarthritis progression occurring after the tibial tuberosity advancement (TTA) procedure. It was hypothesized that the procedure carried out in dogs in the early stages of OA could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Another limitation of the study was that the radiographic examination of the affected joint was not included and possible correlations between radiographic findings and the results of utilizing the tool were not studied. As explained in a previous article, the radiographic assessment of osteoarthritis was not included in the BHSII tool because the signs of osteoarthritis, and their respective radiographic scores, only worsen or stabilize, but not improve, over time (12,15). It would be interesting to relate the BHSII results to osteoarthritis radiographic findings, despite the fact that the functional and the radiographic appearances of the limb do not always correlate (15,16); therefore, other studies from this perspective are suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the study was that the radiographic examination of the affected joint was not included and possible correlations between radiographic findings and the results of utilizing the tool were not studied. As explained in a previous article, the radiographic assessment of osteoarthritis was not included in the BHSII tool because the signs of osteoarthritis, and their respective radiographic scores, only worsen or stabilize, but not improve, over time (12,15). It would be interesting to relate the BHSII results to osteoarthritis radiographic findings, despite the fact that the functional and the radiographic appearances of the limb do not always correlate (15,16); therefore, other studies from this perspective are suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both groups showed significant progression compared to OA at 3 months after surgery, in accordance with the bibliographic data. In fact, it was found that 55% of the treated stifle joints presented progressive OA within 4-16 months of TTA intervention [3,7,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the OA stage, we used a scoring system already validated and described previously [3,20] but modified for this specific study. In particular, we removed the anatomical points relative to the tibial tuberosity from the evaluation, because during TTA it is affected by the osteotomy, and during healing it presents radiographic changes as a function of bone repair of the osteotomy line and integration of the titanium cage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations